2016
DOI: 10.3892/etm.2016.3695
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of high-frequency ultrasound and magnetic resonance imaging in early rheumatoid arthritis

Abstract: Abstract. Early diagnosis and management improve the outcome of patients with rheumatoid arthritis (RA). The present study explored the application of high-frequency ultrasound (US) and magnetic resonance imaging (MRI) in the detection of early RA. Thirty-nine patients (20 males and 19 females) diagnosed with early RA were enrolled in the study. A total of 1,248 positions, including 858 hand joints and 390 tendons, were examined by high-frequency US and MRI to evaluate the presence of bone erosion, bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
1
22
3
Order By: Relevance
“…These investigators observed that 10% of patients had tenosynovitis, and another 10% had joint effusions. Unlike our study, in which no bone erosions were observed by ultrasound, Wang et al observed bone erosions in ultrasound in 5% of RA patients. Another study comparing ultrasound and MRI in the evaluation of early untreated arthritis showed that the predominant ultrasound findings were metacarpophalangeal synovitis (43%), interphalangeal synovitis (53%), and wrist synovitis (63%), thereby demonstrating a similar pattern to that found in CHIKF .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…These investigators observed that 10% of patients had tenosynovitis, and another 10% had joint effusions. Unlike our study, in which no bone erosions were observed by ultrasound, Wang et al observed bone erosions in ultrasound in 5% of RA patients. Another study comparing ultrasound and MRI in the evaluation of early untreated arthritis showed that the predominant ultrasound findings were metacarpophalangeal synovitis (43%), interphalangeal synovitis (53%), and wrist synovitis (63%), thereby demonstrating a similar pattern to that found in CHIKF .…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is similar to some studies, but very different from those found in other series . The predominance of CHIKF in females is also seen in other rheumatological diseases, such as lupus and RA . Also noteworthy is the potential for chronification of the lesions present in our series, given that at least two risk factors cited in the literature (age greater than 45 and female gender) were present in our patients; the third factor, the presence of pre‐existing rheumatological conditions, was standardized as an exclusion criterion in our study …”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…8,9,10 Also, more sensitive imaging tests like high-frequency ultrasonography with power-doppler uptake and extremity magnetic resonance imaging have shown to identify the cases of inflammatory arthritis early before it is clinically apparent. 11,12…”
Section: Introductionmentioning
confidence: 99%